RESERVOIR CHARACTERIZATION AND MONTE CARLO SIMULATION FOR HIDROCARBON ESTIMATION IN BATURAJA FORMATION, GAZA FIELD, SOUTH SUMATRA BASIN - RAFI KUSMAHAWARDHANA, MUHAMMAD
Gaza Field is one of the gas field which is located in South Sumatra Province and exactly located in South Sumatra Basin under operated by PT. Pertamina EP, with the area of 180 km2. This field located in South Palembang sub-Basin which has normal fault structure, with dominant direction is NE – SW. Baturaja Formation is a resevoir in Gaza Field. This study research has a purpose to determine reservoir characteristic such as depositional facies, petrophysical properties and hidrocarbon prospect estimation use Monte Carlo simulation method. The data that use for this reasearch are wireline log from four wells, drill steam test from four wells, cutting data from Gaza 2 Well, core data from Gaza 1 Well and interpreted seismic. From the core data from Gaza 1 Well and cutting data from Gaza 2 Well had result there are 9 limestone litofacies such as Gr, Cr, Cf, Cb, Pcb, Fg, Sm, Fw, and Fp. Baturaja limestone is carbonate isolated platform with shallow marine depositional environtment and the result of the facies asociation are Carbonate Margin Reef and Platform Interior. Based on petrophysical analysis the value of average porosity is 7%. Stochastic method used to determine the hidrocarbon estimation prospect in Gaza Field. It used Monte Carlo simulation method. The result of volumetric calculation are 256 MMSCF at P90 (worst probability), 1506 MMSCF at P50 (most likely probablity) and 6031 MMSCF at P10 (best probablity).